The Role of Social Media in Education: A Case Study of Tertiary Students’ and Lecturers’ Perceptions at a South African University of Technology - Ndukwani, Tiyiselani; Smith, Corle; Rwodzi, Christopher (CV Sinergi Ilmu dan Publikasi, 2025)
The use of social media has affected the landscape of learning and is prompted by the need to communicate using novel Internet platforms. Social media serves as a networking database with a plurality of messages, allowing individuals to be connected. This paper explores the role of social media in education. The research problem stems from the growing integration of social media in educational environments, which raises questions about its effectiveness, challenges, and impact on teaching and learning processes. The lack of a comprehensive understanding of lecturers’ and students’ perceptions creates a gap in incorporating social media in education effectively. It was a qualitative study underscoring the views of a selection of teachers and students. Twelve (12) participants at a University of Technology were sampled purposefully to solicit their views on the role of social media in education. It emerged from the responses of participants that using Facebook had privacy challenges, and opposing views surfaced due to a lack of time to keep tracking friends’ posts. The novelty of this study lies in its comparative exploration of Facebook and WhatsApp as educational tools, highlighting specific challenges like privacy concerns, trolling, and time constraints.